Magneto-Convective Boundary-Layer Flow of a Nanofluid Past Impulsive Vertical Plate with Inclined Magnetic Field. - G. Vijaya Kumar, A.; Gopal Innani, Rahul; R. Pawar, Yash (International Journal of Engineering and Technology, 2018)
The following paper is a study of unsteady hydro-magnetic flow on a boundary layer over an impulsive nanofluid vertical plate in the sight of transverse magnetic field inclined at an angle. The considered fluid is a non-scattering medium and pressure gradient is described by Boussinesqâ€™s approximation and radiative heat flux in the equation of energy. Three types of nanofluids containing Al2O3 engine oil, Boron Engine oil and Graphite engine oil are considered by us. The partial differential equations are converted to dimensionless with particular dimensional quantities and then Laplace transform technique is used to get a closed form solution for velocity and temperature fields without any limits. From the obtained graphs, we studied the changes according to given values of nanofluids on the temperature, transverse velocity, skin-friction and the heat transfer rate at the surface of the wall.Â Â